Congress volume : Basel, 2001 - Lemaire, André, 1942- (Supplements to Vetus Testamentum,, 2002)
This volume publishes the papers given by invitation at the 17th Congress of the International Organization for the Study of the Old Testament, which was held in Basel from 5-10 August 2001. It presents a state of the art of the current exegesis of the Hebrew Bible, taking into account the latest research in general linguistics and semitic philology, as well as textual criticism (Massora Magna, Septuagint, Qumran manuscripts), ethno-sociology and archaeology. Feminist biblical studies are duly represented as well as the last research on literary criticism on the Pentateuch, especially in its relation to other ancient Near Eastern texts (Neo-assyrian and Aramaic inscriptions). Finally, two contributions throw light on the problem of religious interpretation of the Bible (Resurrection of the Dead and Biblical Theology).